Evaluation of the stage classification of anal cancer by the TNM 8th version versus the TNM 7th version. (1st September 2020) - Dahl, Olav; Myklebust, Mette Pernille; Dale, Jon Espen; Leon, Otilia; Serup-Hansen, Eva; Jakobsen, Anders; Pfeiffer, Per; Løes, Inger Marie; Pfeffer, Frank; Spindler, Karen-Lise Garm; Guren, Marianne Grønlie; Glimelius, Bengt; et al.
Abstract: Background : The UICC TNM 7th edition introduced stage groups for anal cancer which in 2019 has not yet come into general use. The new TNM 8th edition from 2016 defines 7 sub-stages. Background data for these changes are lacking. We aimed to investigate whether the new classification for anal cancer reliably predict the prognosis in the different stages. Patients and methods : The Nordic Anal Cancer Group (NOAC) conducted a large retrospective study of all anal cancers in Norway, Sweden and most of Denmark in 2000–2007. From the Nordic cohort 1151 anal cancer patients with follow-up data were classified by the TNM 4th edition which has identical T, N and M definitions as the TNM 7th edition, and therefore also can be classified by the TNM 7th stage groups. We used the Nordic cohort to translate the T, N and M stages into the TNM 8th stages and sub-stages. Overall survival for each stage was assessed. Results : Although the summary stage groups for TNM 8th edition discriminates patients with different prognosis reasonably well, the analyses of the seven sub-stages show overlapping overall survival: HR for stage IIA 1.30 (95%CI 0.80–2.12) is not significantly different from stage I ( p = .30) and HR for stage IIB 2.35 (95%CI 1.40–3.95) and IIIA 2.48 (95%CI 1.43–4.31) are also similar as were HRs for stage IIIB 3.41 (95%CI 1.99–5.85) and IIIC 3.22 (95%CI 1.99–5.20). Similar overlapping was shown for local recurrence and distant spread. Conclusion : The results for the sub-stages calls for a revision of the staging system. We propose a modification of the TNM 8th edition for staging of anal cancer into four stages based on the T, N and M definitions of the TNM 8th classification.